2012
DOI: 10.5455/ijavms.164
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Carcass Characteristics of Helmeted Guinea Fowl (Numida meleagris) FED Varying Levels of Phane Meal (Imbrasia belina) as Replacement of Fishmeal Under Intensive System

Abstract: The objective of this study was to investigate the effect of feeding varying levels of Phane meal (Imbrasia belina) as a protein source on growth performance and carcass characteristics of guinea fowl reared under intensive system up to 13 weeks of age. A total of 96 day old keets were randomly allocated to 4 treatment diets, which were replicated 4 times (n=6/replicate). The inclusion levels of Phane meal in the diets were 4.5%, 9% and 13.5%. Control diet contained 3% fishmeal. Keets were fed 24% CP guinea fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…A lower FCR points to high feed efficiency [65], which could be attributed to better ingredient combination, digestibility, and absorption of nutrients [66]. Contrary to these results, the feed consumption, ADG, FCR, and dressing percentage of guinea fowls fed with 4.5% MWM did not differ from those fed the control diet [51]. These variations in performance could be attributed to the involvement of different species as well as the age and sex of the birds, which are known to produce different results even when birds are offered the same feed [66].…”
Section: Feed Value Of Mopane Worm Mealcontrasting
confidence: 62%
See 1 more Smart Citation
“…A lower FCR points to high feed efficiency [65], which could be attributed to better ingredient combination, digestibility, and absorption of nutrients [66]. Contrary to these results, the feed consumption, ADG, FCR, and dressing percentage of guinea fowls fed with 4.5% MWM did not differ from those fed the control diet [51]. These variations in performance could be attributed to the involvement of different species as well as the age and sex of the birds, which are known to produce different results even when birds are offered the same feed [66].…”
Section: Feed Value Of Mopane Worm Mealcontrasting
confidence: 62%
“…Thus, the supplementation of quail diets with MWM may offer an opportunity to balance and/or enhance the level of essential AA. Some essential AA such as lysine and methionine found in MWM are comparable to those found in fish meal [51]. Table 3 shows that MWM contains all the essential AA needed by quail, which demonstrates that MWM has the potential to replace soybean and fish meals in quail diets.…”
Section: Protein and Amino Acids In Mopane Wormsmentioning
confidence: 77%
“…Thus its inclusion into the diet may balance the indispensable amino acids level. In addition, Nobo et al (2012a) confirmed that levels of some essential amino acids like lysine and methionine in I. belina worm are comparable to fish meal. Whereas, according to Rapatsa and Moyo (2017) the levels of methionine in I. belina exceeded the catfish requirements.…”
Section: Amino Acidsmentioning
confidence: 53%
“…Madibela et al (2006) reported that I. belina worm meal is superior in essential amino acids content compared to soybean and fish meal. Furthermore, Nobo et al (2012a) reported no significant differences in feed intake, ADG, FCR and dressing percentage between guinea fowl fed fish meal (control diet) and 4.5% I. belina worm meal. The differences in Manyeula et al (2013) and Nobo et al (2012a) studies could be ascribed to the used Tswana birds and guinea fowls and their sex differences.…”
Section: Species Fed Diets Containing I Belina Worm Meal Poultrymentioning
confidence: 89%
See 1 more Smart Citation